Pengembangan Kemampuan Berpikir Kritis pada Siswa Sekolah Menengah Pertama (SMP) Berdasarkan Teori Perkembangan Kognitif Jean Piaget - Auliya, Nilazahra (Maliki Interdisciplinary Journal, 2026)
This study aims to examine how Jean Piaget’s cognitive development theory is applied to improve students’ critical thinking skills. Critical thinking skills are skills that need to be developed in learning to overcome life’s problems, while Piaget’s theory explains how students’ cognitive development occurs gradually and influences how they understand and solve problems. This study uses a literature study method by reviewing various sources such as books, journals, and scientific articles. The results of the study show that each stage of Piaget’s cognitive development has a direct relationship to critical thinking skills, especially at the concrete operational and formal operational stages related to analysis, evaluation, and abstract reasoning skills. This study shows that Jean Piaget’s cognitive development theory can be used as a strong foundation for developing learning approaches that encourage the improvement of critical thinking skills in the school environment.